PENGARUH WORD OF MOUTH, KERAGAMAN PRODUK DAN LOKASI DALAM MEMBENTUK MINAT BELI ULANG PADA TOKO ANDIN CEMILAN SITUBONDO DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Rahman, Ervina Adita; Wahyuni, Ika; Praja, Yudha (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Andin Cemilan Situbondo Shop is a snack business that sells retail and wholesale goods. Its location on Bawean Street 1A makes it easy for people to know that this shop sells snacks. The population of this study was all customers who had made purchases at Andin Cemilan Shop. This study’s data analysis and hypothesis testing used the Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of the direct hypothesis test of direct influence using the Smart PLS 3.0 application show that Word of Mouth has a significant positive effect on Consumer Satisfaction, Product Diversity has a positive but insignificant effect on Consumer Satisfaction, Location has a positive but insignificant effect on Consumer Satisfaction, Word of Mouth has a positive and significant effect on Repurchase Intention, Product Diversity has a positive and significant effect on Repurchase Intention, Location has a positive but insignificant effect on Repurchase Intention. The results of the indirect hypothesis test of Word of Mouth have a positive but insignificant effect on Repurchase Intention through Consumer Satisfaction, Product Diversity has a positive but insignificant effect on Repurchase Intention through Consumer Satisfaction, and Location has a positive but insignificant effect on Repurchase Intention through Consumer Satisfaction.